Energy poverty and health: Micro-level evidence from Germany - Martin Buchner; Miriam Rehm (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2025)
This paper aims to understand the health effects of energy poverty in Germany using SOEP panel data from 2010 to 2020. Linear probability models and fixed effects ordered logit models reveal a consistently negative relationship of three expendituresbased energy poverty indicators with general health. The association is stronger for the subjective energy poverty metric: members of households unable to keep the home comfortably warm due to financial reasons have an about 3.23 p.p. lower probability of being in at least satisfactory health. Investigating potential channels shows that mental health is consistently negatively linked to our energy poverty metrics, while physical health is weakly associated with energy poverty in Germany, with the exception of doctor visits. Finally, by instrumenting energy poverty with data on energy price indices and matching energy costs to the heating systems used by households, we show that living in a household that experiences a transition to energy poverty due to rising energy prices is also linked to a lower likelihood of being in good health.
Keywords: I10; I32; Q41; 330; energy poverty; health; fixed effects ordered logit models; Germany